(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to review the physical capacity of 52 students of the Sports Education Study Program of STKIP PGRI Bangkalan class of 2024. The aspects studied include endurance (VO₂Max), muscle strength (push-ups and sit-ups), speed (30 meter run), and flexibility (sit and reach). Results showed that the majority of students had good to excellent endurance (69%), upper and middle body muscle strength in the good to excellent category (77% in push-ups and 79% in sit-ups), and high flexibility (85% in the good or excellent category). However, speed was the most variable aspect, with 13% of students in the deficient category. In general, students’ physical capacity was in the good category, reflecting their readiness to participate in academic activities and sports practices. The results of this study can be the basis for evaluating and preparing a more targeted student physical development program, especially to improve physical components that are still less than optimal.